Price Discovery in the Equity Derivatives Market: A Literature Survey - Pathak, Rajesh; Ranajee,; Kumar, Satish (Indian Journal of Finance, 2014)
Price discovery is the process of incorporating new information to the price of the assets traded at a marketplace and determining the new equilibrium price. When homogeneous or closely linked securities trade at more than one market place, it is important to identify the market where price discovery takes place. Prominent role of derivatives market in price discovery has been recognized in literature by numerous researchers, resulting in conflicting empirical evidence. This study surveys the literature on the role of equity linked derivatives in information diffusion leading to the price discovery of underlying assets. We provide a comprehensive coverage of studies on information content of equity linked derivatives prices and trading activity vis-Ã -vis the direction of price movement and the return volatility of the underlying assets. The existing literature was not found to be in complete agreement about the direction and speed of information flow between the spot market and the equity derivatives markets, however, it substantiates that derivatives should no more be referred to as redundant securities either. The study provides an appendage on how the research area on functions of derivatives has evolved with a focus on its informational role.